Development and validation of HPLC/UV-procedures of secnidazole determination in blood and urine - Shovkova, Oksana; Klimenko, Lina; Shovkova, Zoia; Mykytenko, Olena (ScienceRise: Pharmaceutical Science, 2018)
Aim. The system of HPLC-analyzer MiLiChrome® A-02 is widely used in Ukrainian laboratories of forensic toxicology. The purpose is to apply the HPLC-analyzer system for secnidazole quantitative determination in biological liquids and carry out validation of the developed procedures. Methods. Sample preparation of blood and urine was carried out in three ways – 1) liquid-liquid extraction with organic solvents immiscible with water, 2) amphiphylic solvents extraction and salting-out with ammonium sulphate, 3) complex application of liquid-liquid extraction with organic solvents immiscible with water and amphiphylic solvents extraction with salting-out. Chromatographic conditions: column – Æ2´75 mm, ProntoSIL 120-5-C18 AQ, 5 μm; temperature – 40°С; flow rate – 100 μl/min; Eluent A – 0.2 M LiClO4 – 0.005 M HClO4; Eluent B – acetonitrile; elution mode – linear gradient; detection – UV, 277 nm; volume of injection – 2 μl. Results. Validation of all developed procedures has been carried out by such parameters as specificity, recovery, linearity, accuracy and precision in the variant of the method of standard. The results of analysis have shown the absence of peaks with the retention time, which is coincident with the secnidazole retention time, on the chromatograms of blank-samples for all variants of procedures of analyte isolation. All procedures of sample preparation show the high efficiency of secnidazole isolation both for blood and urine (at the level of 90 %). All examined procedures are characterized by the acceptable parameters of linearity, within-run and between-run accuracy and precision. Conclusions. The set of HPLC-procedures of secnidazole quantitative determination in blood and urine has been developed. Validation of the developed procedures has been carried out; isopropanol application in the acid medium is optimal for biological liquids sample preparation